Serve, Teach, and Lead: It's All About Relationships - Carolyn Crippen (Park University, 2010)
Once a person assumes the mantle of teacher, one becomes a leader, first, in the classroom and then in the school (Crippen, 2005). With this position comes a delicate power and responsibility to the moral imperative. As such, this issue is critical as a component of teacher preparation programs. Goodlad (2004) sounds the alarm that our teacher preparation programs are remiss in responding to the need for moral literacy in our schools. The following paper will introduce the philosophy of servant-leadership, a moral way of serving, as defined by Robert K. Greenleaf (1970/1991) and will respond to Goodlad's call with possibilities for preservice teachers that help them examine and define their role in contributing to the common good through servant-leadership.